Chinese Corporate Players in the South China Sea: Complicating the Disputes? - Gong, Xue (2016)
China’s state-owned enterprises are increasingly engaged in various activities in the South China Sea. Their involvement, usually mingled with nationalism in China, further complicates Beijing’s policy on the dispute.